A viability criterion for computer system development projects - J. Mende (South African Journal of Business Management, 1984)
A manager facing the decision whether to proceed with a proposed computer system development project needs to determine whether its benefits are worth more than its costs. This can be done by applying a simple mathematical formula to calculate the project's 'net worth', as the sum of the annual benefits obtainable during the system's life span, less its development costs. The formula recognizes that a system's annual benefit, comprising enhanced informational value plus reduction In data processing cost, will change as a result of obsolescence, cost of capital, organizational growth and learning.
Keywords: 650